Paradigms of Movement Composition - Dahlstedt, Ami Sk (The International Journal of Screendance, 2014)
My background is that of a dancer. Since childhood I have also been a storyteller. This made it difficult for me to understand why there had to be such a sharp line between dance and theater, between magic and realism, between movement and text. Is that line about to be erased?